Migration, Wage Labor, and Domestic Relationships: Immigrant Women Workers in Montréal - Meintel, Deirdre; Labelle, Micheline; Turcotte, Geneviève; Kemineers, Marianne (Anthropologica, 2022)
As part of the study on the economic and social insertion of immigrant women workers into Quebec society, women of four ethnic origins were interviewed. It was found that while immigration had allowed women to make greater financial contributions to the household than before, men's participation in domestic tasks was mostly limited to child care when necessitated by women's outside work. Budgetary patterns tend to obscure the importance of women's financial contributions insofar as decision-making is concerned. Nonetheless, their new wage earning capacity is seen as positive by the women studied. Overall, our data tend to confirm the findings of numerous other studies of non-immigrant populations in North America to the effect that wage work by women does not necessarily lead to egalitarian domestic relationships.